2014
DOI: 10.1021/ma401673n
|View full text |Cite
|
Sign up to set email alerts
|

13C MAS NMR Study of Poly(methacrylic acid)–Polyether Complexes and Multilayers

Abstract: Hydrogen-bonded interpolymer complexes are widely used as stimuli-responsive materials. This solid-state 13 C MAS NMR spectroscopy study examines the influence of water and temperature on the hydrogen bond structures of 13 C-labeled poly(methacrylic acid) (PMAA) complexes with poly(ethylene oxide) (PEO) and poly(vinyl methyl ether) (PVME). The spatial variation of the inter-and intrapolymer hydrogen bonds in the dried bulk complexes and supported multilayers was measured by 2D 13 C exchange (EXSY) NMR. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The average diameter of MHH particle was determined [ 70 ]. Then, the values of D p and D f were calculated under the given conditions explained below.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average diameter of MHH particle was determined [ 70 ]. Then, the values of D p and D f were calculated under the given conditions explained below.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the values of D p and D f were calculated under the given conditions explained below. R p (m) is the average radius of the adsorbent particles, ε is the film thickness (10 −5 m) [ 70 ] and C s and C L are the concentration of adsorbate in solid and liquid phase, respectively. Debnath et al [ 70 ] assumed that the intraparticle diffusion will be the rate-limiting step if the calculated intraparticle diffusion coefficient ( D p ) value is in the range 10 −15 –10 −18 m 2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 C peaks of HPMC and EUD-S were assigned based on previous reports. 18,33 The change in the chemical shift of 13 C peaks of HPMC was small among polymer SPDs, while the peak shapes of C β , C γ , C δ , and C ε of HPMC were slightly changed by EUD-S blending; the peak width of HPMC at approximately 70−90 ppm was sharper for HPMC/EUD-S SPD than for HPMC SPD. This result is in agreement with a previous report that indicated that the hydrogen bonds among the hydroxyl groups of HPMC were disrupted by the molecular interaction between HPMC and EUD-S, leading to a change in the peak shape of HPMC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The carbonyl group of the methyl methacrylate of EUD-S is likely involved in the nondimer structure. 33 In our previous study, the relative carbonyl peak areas of the cyclic-and open-dimer structures at 186.3 and 180.4 ppm in EUD-S were reduced in comparison with that of the nondimer structure at 177.7 ppm by HPMC blending with EUD-S. 18 The polymer blending of HPMC with EUD-S led to the formation of hydrogen bonds between HPMC and EUD-S, which resulted in the cleavage of the dimeric structure of methacrylic acid in EUD-S. In the present study, it was demonstrated that the dimer structure in EUD-S was cleaved depending on the amount of HPMC in HPMC/EUD-S SPD.…”
Section: ■ Results and Discussionmentioning
confidence: 99%